Ecological, evolutionary, and conservation implications of incubation temperature‐dependent phenotypes in birds. (1st February 2013) - DuRant, Sarah E.; Hopkins, William A.; Hepp, Gary R.; Walters, J. R.
ABSTRACT Incubation is a vital component of reproduction and parental care in birds. Maintaining temperatures within a narrow range is necessary for embryonic development and hatching of young, and exposure to both high and low temperatures can be lethal to embryos. Although it is widely recognized that temperature is important for hatching success, little is known about how variation in incubation temperature influences the post‐hatching phenotypes of avian offspring. However, among reptiles it is well known that incubation temperature affects many phenotypic traits of offspring with implications for their future survival and reproduction. Although most birds, unlike reptiles, physically incubate their eggs, and thus behaviourally control nest temperatures, variation in temperature that influences embryonic development still occurs among nests within a population. Recent research in birds has primarily been limited to populations of megapodes and waterfowl; in each group, incubation temperature has substantial effects on hatchling phenotypic traits important for future development, survival, and reproduction. Such observations suggest that incubation temperature (and incubation behaviours of parents) is an important but underappreciated parental effect in birds and may represent a selective force instrumental in shaping avian reproductive ecology and life‐history traits. However, much more research is needed to understand how pervasive phenotypic effects of incubation temperature are among birds, the sources of variation in incubation temperature, and how effects on phenotype arise. Such insights will not only provide foundational information regarding avian evolution and ecology, but also contribute to avian conservation.